Indigenization and Legitimization of Local Government Authorities in Tanzania: A Historical Account - Marijani, Ramadhani; Milanzi, Montanus C. (Journal of Policy and Leadership, 2022)
This article reports on the state of indigenization and legitimation of Local Government Authorities in Tanzania. A systematic historical review approach was conducted to trace the major public administration practices that influenced and shaped the trends and the responsible institutions in Tanzania. The findings indicate that past practices have a significant impact on the administration of the states at the local level of governance. Thus, the institutional distortions theory demonstrates that the colonial native administrative system imposed on Tanganyika created institutional errors whose distractions affected the capacity of actors in making rational decisions regarding the choices of institutions. Because of these distractions, the possibility of choosing the right institutions for postcolonial Tanzania was a herculean task. The pre-colonial bureaucratic African administration strand of the African Public Administration theory informs us that the administration during the pre-colonial era was highly decentralized with very few centralized polities. This indicates that pre-colonial Africa had a robust system of local governance. We conclude that the past interventions in local government systems could have created a form of government not intended by independent Tanzania.